2017
DOI: 10.14713/pcsp.v13i3.2015
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Limitations of Internet-Based Cognitive-Behavioral Treatments for Anxiety Disorders

Abstract: This commentary discusses the strengths and limitations of internet-based cognitive-behavioral treatments (ICBT) for anxiety disorders, as highlighted by the case studies described in Ciuca, Berger, and Miclea (2017), and in Schulz, Vincent, and Berger (2017). In comparing the course of treatment for patients with contrasting clinical outcomes, the authors offer insights into the many benefits and challenges of ICBT. Suggestions for improving ICBT interventions for anxiety disorders, implications for implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Stronger therapeutic alliance is associated with better outcomes in CBT for SAD (Hays, Hope, VanDyke, & Heimberg, 2007), and face-to-face intervention offers opportunities for modification to the individual needs of the client, such as in terms of motivation for treatment, which could lead to better alliance compared to internet interventions. Furthermore, clinicians seeing clients in-person can offer feedback about interpersonal skills and provide opportunities to practice skills that the client perceives as defective (Schulz, Vicent, & Berger, 2017;Woods, Stults, Terry, & Rego, 2017).…”
Section: Psychological Distressmentioning
confidence: 99%
“…Stronger therapeutic alliance is associated with better outcomes in CBT for SAD (Hays, Hope, VanDyke, & Heimberg, 2007), and face-to-face intervention offers opportunities for modification to the individual needs of the client, such as in terms of motivation for treatment, which could lead to better alliance compared to internet interventions. Furthermore, clinicians seeing clients in-person can offer feedback about interpersonal skills and provide opportunities to practice skills that the client perceives as defective (Schulz, Vicent, & Berger, 2017;Woods, Stults, Terry, & Rego, 2017).…”
Section: Psychological Distressmentioning
confidence: 99%
“…The reasons for not seeking treatment include existing barriers such as: financial costs, travel time needed to attend face-to-face treatments, fear of being stigmatised and peer rejection (Ebert et al, 2015). Internet-based interventions have been shown to be effective in overcoming some of these limitations (Woods et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, people with social anxiety can experience chronic worries when having to deal with others, including interacting with counsellors who help them overcome their anxiety disorder (Woods et al, 2017). There is a need for a strategy that connects those who suffer social anxiety with counsellors without them having to conduct face-to-face counselling.…”
mentioning
confidence: 99%
“…The internet allows counsellors and clients to interact and hold counselling sessions without a face-to-face meeting. Although online counselling cannot replace face-to-face counselling, it is an available option which can serve as the initial step in overcoming social anxiety (Woods et al, 2017). In a study by McKenna, Green, and Gleason (2002), participants who had social anxiety reported that they experienced decreasing levels of social anxiety after interacting with other people online for two years.…”
mentioning
confidence: 99%
See 1 more Smart Citation